Improving the management of patients with meniscal lesions of the knee - Abram, SGF (2019)
Meniscal lesions in the knee are common and keyhole surgery to excise a meniscal tear, arthroscopic partial meniscectomy (APM), is one of the most commonly performed orthopaedic surgical procedures worldwide. Despite the frequency with which the procedure is performed, the effectiveness of the procedure has been challenged by the publication of a series of clinical trials reporting similar outcomes following physiotherapy or placebo surgery. The broad aims of this thesis were (1) to determine trends and variation in the use of APM and consider if there is evidence for potential overuse of the procedure, (2) to systematically appraise the effectiveness of APM in different patient groups, (3) to determine the potential risks associated with undergoing APM, and (4) to deliver standardised descriptive terminology and treatment guidance informed by this new research.